The Rubbish Hero : RE3 . (Derry The Source - Play-Art Materials Centre)
Re3 is a rubbish hero who forms magically out of waste and lives in the 'Source'. Here he rescues waste and teaches kids the importance of reducing, reusing and recycling.
- Category: animation
- Documentaries made in Northern Ireland